Initial evaluation of a new plastic pancreatic duct stent for endoscopic ultrasonography-guided placement - Itoi, Takao; Sofuni, Atsushi; Tsuchiya, Takayoshi; Ishii, Kentaro; Ikeuchi, Nobuhito; Tanaka, Reina; Umeda, Junko; Tonozuka, Ryosuke; Honjo, Mitsuyoshi; Mukai, Shuntaro; Takayama, Takako; Moriyasu, Fuminori (Endoscopy, 2015)
There are currently no plastic pancreatic duct stents that have been designed for endoscopic ultrasonography (EUS)-guided placement. This study prospectively evaluated the feasibility and efficacy of a new, single-pigtail, plastic stent. Eight patients with main pancreatic duct stricture or stenotic pancreatojejunostomy underwent EUS-guided placement of the pancreatic duct stent. The stent was placed successfully in all cases (8/8). Treatment success was achieved in all cases (8/8). A mild adverse event associated with the procedure was observed in one patient but there were no other adverse events during a mean follow-up of 7.4 months. This new pancreatic duct stent appears to be feasible and effective for EUS-guided stenting.